DEICITY AND MORPHOSYNTAX OF DEMONSTRATIVES IN KIMBUNDU:: ANALYSIS OF THE GRAMMAR OF DIAS AND CHATELEAIN - Paranhos, Ramon Arend (2024)
In this study, I analyze the interpretations of demonstratives in two Kimbundu grammars Dias (1667); and Chatelain (1889). I assume Lyons (1999), Diessel (1999), Guardiano (2009) e Levinson (2018) to describe semantic, pragmatic, and morphosyntactic properties of demonstratives. I assumed that the two grammars would have similar descriptions, but I identified divergences in the quantity and oppositions of demonstratives. These divergences can be explained mainly by extralinguistic factors, such as the perception or importance of the phenomenon; the development of printing techniques, grammatical characterization, and the evolution of scientific studies; and the purpose of producing grammars. Intralinguistic factors, such as linguistic change and variation, are not conclusive.